Variation Management in Construction Contracts: A Comparative Study of PWD 203A (Rev. 01/2010) and PAM 2018 - Mohamed Ishak, Mohamed Suhaini; Zulhabri Ismail (Journal of Technology Management and Business, 2025)
The Malaysian construction and development sector plays a vital role in driving national economic growth. Yet, project performance often suffers when stakeholders manage variations ineffectively, causing delays and reducing overall efficiency. Variations in major contracts typically result in financial overruns and extended project durations. Though standard contracts outline procedures, inconsistent application often leads to disputes and operational inefficiencies. Empirical evidence highlights the dynamic and uncertain nature of variation practices, wherein inadequate implementation exacerbates risks to project outcomes. This research seeks to offer a thorough insight in best practice through a comparative examination of Malaysia’s prevalent standard forms of contracts (SFOC), PWD 203A (Rev. 01/2010) and PAM 2018. This research aims to investigate the current variation management procedures outlined in PWD 203A (Rev. 01/2010) and PAM 2018, assess effective variation control methods, and formulate best practice models. A dual methodology was employed, which integrated comprehensive document reviews and semi-structured interviews with six interviewees: two project managers, one architect, one contract administrator, one contract manager, and one consultant from industry professionals, all contributing to a robust contractual analysis. Comparative analysis employs four strategies, which will be examined and supported by academic sources, professional standards, and contractual documentation from 2010 to 2024. Findings aim to reveal success determinants in effective communication, rapid decision-making, and contractual clarity enhancing variation governance and efficiency.